5G network intelligent scheduling based on core network analysis and decision - Qingyang WANG; Zhibin YANG; Biao LONG; Haoquan LIANG (Dianxin kexue)
Larger bandwidth and complex technology of the 5G networks inevitably bring a significant increase in overall energy consumption, so green energy-saving of mobile networks has attracted widespread attention.The long-term coexistence of 5G and 4G, as well as the wide coverage of low-frequency and the wide bandwidth characteristics of high-frequency of 5G, enable different types of services to be carried by different carriers of 5G or 4G respectively.Based on the above considerations, a 5G network intelligent scheduling scheme based on corenetwork analysis and decision was proposed, which could schedule different types of services to different radio access and frequencies for carrying, so as to achieve service assurance and energy-saving.Simulation results reveal that, compared with the existing schedule scheme within radio access network, 5G network intelligent scheduling has advantages in energy saving while ensuring quality of service.Finally, the progress of international standardization of 5G network intelligent scheduling was introduced.